49.25% efficient cyan emissive sulfur dots via a microwave-assisted route. Issue 29 (4th May 2020) - Hu, Zhe; Dai, Hanqing; Wei, Xian; Su, Danlu; Wei, Chang; Chen, Yuanyuan; Xie, Fengxian; Zhang, Wanlu; Guo, Ruiqian; Qu, Songnan
Abstract : The cyan emissive sulfur dots with a record high PL QY of 49.25% were successfully synthesized via a microwave-assisted route. Abstract : Cyan emissive sulfur dots with a record high photoluminescence (PL) quantum yield of 49.25% have been successfully prepared via a microwave-assisted top-down route. The PL enhancement induced by electrostatic repulsion of sulfite groups and steric hindrance of polyethylene glycol 400 (PEG-400) were investigated for the first time.